Epidemiology of malaria and the distribution of genetic markers associated with drug resistance in Mawza district, Taiz governorate, Yemen / Lina Mohammed Qaid Al-Areqi - Lina, Mohammed Qaid Al-Areqi (2017)
In Yemen, malaria is still one of the most serious health problems, with 149,451 cases being reported in 2013. Of these, Plasmodium falciparum represents 99%. It is estimated that 25% of the population are at high risk and a total of 37,763 microscopy confirmed and 29,750 rapid diagnostic tests (RDTs)-confirmed cases were reported in 2014. The present study aimed to determine malaria prevalence and its associated risk factors in rural communities of Taiz governorate as well as to determine the knowledge, attitude and practices (KAP) of the local populations toward malaria. The study also aimed at evaluating the light microscopy (LM) and an RDT, combining both P. falciparum histidine-rich protein-2 (PfHRP-2) and Plasmodium lactate dehydrogenase (pLDH), for falciparum malaria diagnosis against nested polymerase chain reaction (PCR) as the reference method. The last objective of the study was detecting the molecular markers (Pfcrt K76, Pfmdr-1 N86, Kelch13, Pfdhfr and Pfdhps) of P. falciparum resistance to chloroquine, artemisinin and sulphadoxine/pyrimethamine respectively. A household-based, cross-sectional malaria survey was conducted in Mawza District, a malaria-endemic area in Taiz governorate during the transmission season from October 2013 to April 2014. Blood specimens were collected from 488 participants and examined by LM and PfHRP-2/pLDH RDT. Samples positive using LM and/or PfHRP-2/pLDH RDT were confirmed using PCR to exclude the false positive results. Nested PCR followed by digestion was used for detection of mutations at position 76 in pfcrt and 86 in pfmdr-1. Mutations in the Kelch13, dhfr and dhps genes at specific codons were determined by nested PCR and followed by gene sequencing. Malaria prevalence rate based on PCR-adjusted RDT was 25.5% (95% CI: 21.6 29.5). Sub-microscopic malaria was significantly more prevalent among non-febrile individuals (16.0%; 95% CI: 12.88ï¿½19.75). Comparison between LM and PfHRP-2/pLDH RDT showed that the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of PfHRP-2/pLDH RDT were 96.0% (95% CI: 90.9-98.3), 56.0% (95% CI: 44.7-66.8), 76.3% (95% CI: 69.0-82.3) and 90.4% (95% CI: 78.8-96.8), respectively. Fifty (50) falciparum positive samples were selected for detection of mutations at codon K76T of the Pfcrt gene and codon N86Y of the Pfmdr-1 gene. The Pfcrt gene was exclusively mutant allele and Pfmdr-1 gene was wild type allele. The dhfr 51I/108N double mutant allele was found in one isolate and regarding Kelch13 and dhps, all isolates were of wild type alleles. In conclusion, the present study revealed a higher proportion of sub-microscopic malaria infections among rural populations of Mawza than that can be detected by LM, particularly among asymptomatic participants. This represents a significant reservoir of infection and its on-going transmission should be considered when tailoring future control and elimination strategies. The PfHRP-2/pLDH RDT showed high sensitivity for the survey of falciparum malaria including asymptomatic malaria cases. artemisinin combination therapy (ACT); Artemisinin plus sulphadoxine/pyrimethamine (ART+SP) still has a high efficacy. The fact that all isolates had mutant allele of pfcrt 76T may indicate the continued usage of chloroquine (CQ) for treating malaria.